Increasing Arabic Language And Culture Literature Capabilities For Nasyiatul Aisyiyah Sidoarjo : Peningkatan Kemampuan Literasi Bahasa Dan Budaya Arab Untuk Kader Nasyiatul Aisyiyah Kabupaten Sidoarjo - Hikmah, Khizanatul; Romadlon, Dzulfikar Akbar; Ammar, Farikh Marzuki (Procedia of Social Sciences and Humanities, 2022)
The development of information technology and social media has an impact on accelerating cultural exchange, this is not accompanied by an acceleration of literacy, especially Arabic literacy. There is an assumption that things that smell Arabic are considered as symbols of Islam, for this reason this abdimas aims to provide literacy training in Arabic language and culture for Nasyiatul Aisyiyah cadres, the Nasyiatul Aisyiyah, Sidoarjo. it is hoped that later they will provide literacy insights that have an impact that is not easily consumed by news. hoaxes and can provide enlightenment to the community, especially in the Arabic language field. This activity is carried out with a workshop or literacy camp model as well as seminars on Arabic language and culture in the nuances of Christian culture. The results of the pre-test assessment showed that 85% of the participants could not distinguish between language literacy and Islamic culture originating from the Qur'an and general Arabic cultural literacy which had nothing to do with the Qur'an, while the post-test results showed 95% participants can sort out things related to Islam and Arabic culture.